(untitled) (Research, Society and Development, 2021)
The objective of this essay is to delimit an analytical scheme on International Trafficking in Persons (ITP), considering its peculiarities, in search of a sociological and juridical conception that assesses the notion of the trafficked person and the status of the victim. Methodologically, we undertake an exploratory study, in order to achieve a descriptive objective, based on bibliographic, documentary and statistical procedures. Thus, we delimit the need for the articulation of several social, political and economic elements that can account for a multifaceted, economical, sociological and political phenomenon that affect the ways in which ITP takes root in the structure of a country. We therefore developed a conceptual, sociological-legal and political tripartite scheme. The three schemes can allow a more accurate reading of a crime no longer read under just one lens. We refer to the idea that a political conception of International Trafficking in Persons demands a sociological conception that analyzes social dynamics, with a view to guaranteeing the victim’s rights, in order to stop this crime.